Quenchability improvement and control simplification by ice mandrel in hot stamping of ultra-high strength steel hollow parts. (April 2021) - Talebi-Anaraki, Ali; Maeno, Tomoyoshi; Ikeda, Ryohei; Morishita, Kazui; Mori, Ken-ichiro
Graphical abstract: Highlights: Hot stamping of tubes using an ice mandrel and resistance heating was developed. The proposed process does not require an internal pressure control system. The thermal insulation of ice mandrel improved both heating and forming behaviors. The die quenching of tubes was significantly enhanced by using the ice mandrel. Ultra-high strength steel hollow products having above 400 HV10 can be produced by hot stamping using the ice mandrel. Abstract: To produce ultra-high strength steel hollow parts for reducing the body weight and improving the collision safety of automobiles, a hot stamping process of quenchable steel tubes using ice mandrel and resistance heating was developed. To solve the problem of buckling and low cooling rate during stamping of hollow products, an ice mandrel was inserted in the tube. The effect of the ice mandrel on heating and forming behavior was investigated. Quenchable ice-filled steel tubes were able to heat over austenitizing temperature by adding papers as thermal insulation. Moreover, the ice mandrel simplifies the controlling process by generating a reaction force to prevent the buckling and increase the hardness after die quenching of the ice-filled tubes. Using the ice mandrel with insulating papers is significantly effective to produce ultra-high strength hollow products.